Environmental radiation in the route Amazons Center (Lima-Tingo María) - Manosalva Bacigalupo, Julio (2010)
We have carried out measurements ionizing radiation in equivalent dose in towns understood in the highway Lima - Tingo María, approximately 525 Km, with altitudes that are from 154 until the 4818 metres above sea level (Anticona). Crossing four political regions of the center of the Peru (Lima, Junín, Pasco and Huánuco). The detected radiations have a range from 171 to 602 nSv/h, with an average of 367 nSv/h. the biggest count is obtained in Casapalca, Anticona, Morococha and surroundings, Tinyahuarco, Ricrán and Huayllay.